Geomorphological study of the origin of Mongolian Altai Mountains Lake depressions: implications for the relationships between tectonic and glacial processes - Altanbold Enkhbold; Ulambadrakh Khukhuudei; Yeong Bae Seong; Yumchmaa Gonchigjav; Li Dingjun; Byambabayar Ganbold (Mongolian Geoscientist)
The lake depressions in the Mongolian Altai Mountains, and the issues related to their formation have yet to be thoroughly examined in previous research. Previous studies primarily focused on the paleogeographical evolution and glaciation dynamics of the Altai Mountains. This study presents relationships between tectonic and glacial processes that have formed the lake depressions, such as Khoton, Khurgan, Dayan, Khar (western), and Khar (eastern) in the Mongolian Altai Mountains. The depressions of Khoton, Khurgan, and Dayan lakes are situated along regional fault zones, extending in an northwest-southeast direction, forming intermontane depressions directly connected to the Mongolian Altai Mountains. However, the depressions of Dayan, Khar (western), and Khar (eastern) lakes have been dammed by moraine deposits in the near portion of the depression. The compliance matrix of tectonic geomorphological criteria indicates that the Khoton, Khurgan, Dayan Lake, and Khar (western) Lake depressions are more than 50% compatible. Similarly, the compliance matrix for glacial  eomorphological criteria indicates more than 60% compliance for all lake depressions. The Mongolian Altai intermontane depressions are thus of tectonic origin, whereas the lakes have a glacial origin, resulting from dammed moraine sediments. The significance of this work lies in demonstrating how geomorphological research can be employed to provide a detailed understanding of the pattern of lake depressions.